Microcornea and Thickened Lens in Angle Closure following Nonsurgical Treatment of Retinopathy of Prematurity - Chang, Ta C. (J Ophthalmol, 2020)
PURPOSE: To characterize the clinical features in young patients with angle closure and to determine the characteristics associated with acquired anterior segment abnormality following retinopathy of prematurity (ROP) treatment. METHODS: We performed two retrospective case-control series. In the first series, we identified consecutive young angle closure patients without prior surgeries, with and without a history of ROP treatment; in the second series we identified consecutive patients who underwent ROP treatment, without and without anterior segment changes. RESULTS: In the first series, 25 eyes of 14 consecutive angle closure patients were included: 19 eyes (11 patients, 78.6%) had a history of treated ROP, while 6 eyes (3 patients) belonged to full-term patients. The treated ROP eyes had significantly shallower anterior chambers (1.77 ± 0.17 mm vs 2.72 ± 0.18 mm, P < 0.0001) and thicker lenses (5.20 ± 0.54 mm vs 3.98 ± 0.20 mm, P = 0.0002) compared to the full-term controls. In the second series, 79 eyes of 40 patients were included, with median gestational age of 24.6 weeks. Acquired iridocorneal adhesion was noted in the eight eyes (10.1%) at a mean age of 4.7 years and was associated with prior zone 1 and plus disease (P = 0.0013), a history of initial intravitreal bevacizumab treatment (IVB, P = 0.0477) and a history of requiring additional IVB after initial treatment (P = 0.0337). CONCLUSIONS: Many young angle closure patients may have a history of treated ROP and may present with the triad of increased lens thickness, microcornea, and angle closure.